PERAN PESANTREN DALAM MEMPERTAHANKAN BUDAYA ISLAM DI ERA PANDEMI COVID-19 DI PONDOK PESANTREN AL QOMARIAH KECAMATAN GALANG KABUPATEN DELI SERDANG - Parlaungan Lubis, Widya Ningsih, Nurdiani, (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2022)
Pesantren is the oldest education system that is unique, especially in Indonesia, which has character and is quite proud because pesantren is an educational institution that teaches Islam and contributes to the development of whole human beings. The education is given in a bandungan way where the mu'allim/ah teach students based on books written in Arabic and the students/women live in boarding schools. This study discusses Islam and culture. Islam has two aspects, namely the religious aspect and the cultural aspect. Thus, there is an Islamic religion and there is an Islamic culture. The problem is how the efforts of pesantren in maintaining Islamic culture in the pandemic era and what changes before and after the pandemic in implementing Islamic culture in pesantren. This research was conducted in Kotangan village, Galang district, Deli Serdang regency. The research conducted by the author is a descriptive field research, which merely describes accurately the Islamic culture in the Al-Qomariah Galang Islamic boarding school. The type of research used is qualitative. Data collected through observation and interviews. The results of research conducted by researchers prove that there are visible changes in the implementation of Islamic culture in Islamic boarding schools during the current pandemic.